Effects of Intravenous Infusion With Sodium Butyrate on Colonic Microbiota, Intestinal Development- and Mucosal Immune-Related Gene Expression in Normal Growing Pigs - Chen, Xue; Xu, Jumei; Su, Yong; Zhu, Weiyun (Frontiers in Microbiology, 2018)
This study aimed to investigate effects of intravenous infusion with sodium butyrate (SB) on colonic microbiota, intestinal mucosal immune and intestinal development in normal growing pigs. Twelve crossbred barrows (Duroc × Landrace × Large White) fitted with a medical polyethylene cannula via internal jugular vein were daily infused with 10 ml sodium butyrate (200 mmol/l) or the same volume of physiological saline for 7 d. Results showed that SB infusion had no effects on the short-chain fatty acids concentrations and the number of total bacteria, but significantly increased the microbial richness estimators (ACE and Chao1), and the abundance of genera related to Clostridiales order in the colonic digesta (P < 0.05). SB infusion significantly up-regulated the mRNA expression of monocarboxylate transporter 1 (MCT1) in the colon, while no change was found in the ileum. Only the relative mRNA of pro-inflammatory cytokine IL-6 gene was decreased significantly in the ileum by SB infusion. On the contrary, in the colon, SB infusion significantly decreased the gene expression of histone deacetylase 1 (HDAC1) and pro-inflammatory cytokinesIL-6, IL-18, IL-12p40 and TNF-α (P < 0.05), but significantly increased the sIgA concentration, the gene expression of anti-inflammatory cytokineIL-10, and the expression of intestinal development-related gene zonula occludens-1 (ZO-1), occludin and epidermal growth factor (EGF) (P < 0.05). The results suggest that systemic SB can modify colonic microbial composition, regulate the inflammatory cytokine- and intestinal development-related gene expression in pigs under the normal physiological condition. This study may provide an alternative strategy for improving the intestinal health of normal piglets.